Fine structural and photoluminescence properties of Mg2Si nanosheet bundles rooted on Si substrates. (10th February 2021) - Koga, Tomoya; Tamaki, Ryo; Meng, Xiang; Numazawa, Yushin; Shimura, Yosuke; Ahsan, Nazmul; Okada, Yoshitaka; Ishida, Akihiro; Tatsuoka, Hirokazu
Abstract: Creating vertically aligned 2D nanostructures is a promising approach to achieving advanced electronic and optoelectronic materials. In this study, Mg2 Si nanosheet bundles were synthesized by Ca atom extraction from CaSi2 microwalls grown on Si substrates via thermal annealing in a MgCl2 /Mg mixed vapor. The nanosheet bundle structure was modified to compound nanosheet bundles from previously reported Si nanosheet bundles. The observed Mg2 Si nanosheets consist of thin Mg2 Si layers, and well-defined fine-scale Mg2 Si superlattice-like structures were achieved in the nanosheet bundles. In addition, the Raman scattering and photoluminescence properties were examined, and structural and electronic modifications of the nanosheet bundle compared with the bulk crystals were suggested. To obtain tailored properties and functionalities of the nanosheet bundles, structural modification of layered crystals is a useful technique.